Baseline Testosterone Predicts Body Composition and Metabolic Response to Testosterone Therapy - Deepika, FNU; Ballato, Elliot; Colleluori, Georgia; Aguirre, Lina; Chen, Rui; Qualls, Clifford; Villareal, Dennis T.; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2022)
Context: Male hypogonadism adversely affects body composition, bone mineral density (BMD), and metabolic health. A previous report showed that pre-treatment testosterone (T) levels of <200 ng/dL is associated with greater improvement in spine BMD with T therapy. However, to date, there is no study investigating whether baseline T levels also influences body composition and metabolic response to T therapy. Objective: To determine if there are differences in the changes in body composition, metabolic profile, and bone turnover markers, in addition to BMD, in response to T therapy in men with baseline T level of < 264 ng/dL compared to those with levels ≥264ng/dL. Methods: Secondary analysis of single-arm, open-label clinical trial (NCT01378299) on pharmacogenetics of response to T therapy conducted between 2011-2016 involving 105 men (40-74 years old), with average morning T <300 ng/dL, given intramuscular T cypionate 200 mg every 2 weeks for 18 months. Subjects were divided into those with baseline T levels of < 264 ng/dL (Group 1, N=43) and those with ≥264 ng/dL (Group 2, N=57). T and estradiol (E2) were measured by liquid chromatography/mass spectrometry; serum bone turnover markers (C-telopeptide [CTX], osteocalcin, sclerostin), adiponectin, and leptin by enzyme-linked immunosorbent assay; glycated hemoglobin (HbA1c) by high-performance liquid chromatography, areal BMD, and body composition by dual-energy x-ray absorptiometry (DXA). Results: Group 1 showed greater increases in appendicular fat-free mass (FFM) at 6 and 18 months (P=0.03 and P=0.04, respectively) and total FFM at 18 months compared to Group 2 (P=0.05). Both groups had significant loss of total and regional fat mass and increase in total and regional lean mass. Group 2 showed significant decreases in fasting glucose at 18 months (P=0.04), HbA1c at 12 months (P=0.005), and LDL(P=0.03) at 6 months compared to Group 1. Leptin declined significantly at 18 months in Group 2 compared to Group 1(P=0.03). No significant differences in BMD and bone turnover markers were observed. Conclusion: T therapy results in improvement in body composition irrespective of baseline T levels but T <264 ng/dL is associated with greater improvement in FFM; whereas T level of ≥264 ng/dL favors improvement in metabolic profile.